Slx1-Slx4 Are Subunits of a Structure-specific Endonuclease That Maintains Ribosomal DNA in Fission Yeast - Coulon, Stéphane (The American Society for Cell Biology, 2004)
In most eukaryotes, genes encoding ribosomal RNAs (rDNA) are clustered in long tandem head-to-tail repeats. Studies of Saccharomyces cerevisiae have indicated that rDNA copy number is maintained through recombination events associated with site-specific blockage of replication forks (RFs). Here, we describe two Schizosaccharomyces pombe proteins, homologs of S. cerevisiae Slx1 and Slx4, as subunits of a novel type of endonuclease that maintains rDNA copy number. The Slx1-Slx4–dependent endonuclease introduces single-strand cuts in duplex DNA on the 3′ side of junctions with single-strand DNA. Deletion of Slx1 or Rqh1 RecQ-like DNA helicase provokes rDNA contraction, whereas simultaneous elimination of Slx1-Slx4 endonuclease and Rqh1 is lethal. Slx1 associates with chromatin at two foci characteristic of the two rDNA repeat loci in S. pombe. We propose a model in which the Slx1–Slx4 complex is involved in the control of the expansion and contraction of the rDNA loci by initiating recombination events at stalled RFs.